Pendidikan Nonformal sebagai Garda Depan Pencegahan Cybergrooming: Sebuah Systematic Literature Review (SLR) dengan Perspektif Psikologi Sosial - Maysara, Siska Resti (Lembaga Yasin AlSys, 2025)
The limited number of studies on cybergrooming and its prevention through non-formal education forms the background of this research, despite the significant implications of this phenomenon for adolescent protection in the digital era. This study aims to analyze the phenomenon of cybergrooming, identify psychosocial factors that increase adolescent vulnerability, and examine the role of non-formal education in its prevention. The method employed is a qualitative Systematic Literature Review (SLR), with 19 selected articles from an initial 155 publications using the PICOC framework and the PRISMA flow. Data were analyzed through thematic content analysis. The findings indicate that major risk factors include low digital literacy, limited social skills, family pressures, and the need for self-identity. The dynamics of grooming align with social learning, social identity, and social exchange theories, underscoring that cybergrooming is a systematic form of social manipulation rather than merely an individual behavior. The study concludes that non-formal education plays a strategic role in building digital literacy, strengthening psychosocial resilience, and creating safe spaces for adolescents through community-based approaches, peer education, and parental involvement. The implications of this study include theoretical contributions to the literature on cybergrooming from a social psychology perspective, as well as practical recommendations for policymakers and educators to reinforce the role of non-formal education as a preventive instrument. Future research is recommended to empirically test the effectiveness of such educational interventions across different social contexts.